FREQUENCY OF UNDIAGNOSED THYROID DISORDERS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT A TERTIARY CARE CENTER - Khan, Rab Nawaz; Ullah, Raza; Ahmad, Ibrar; Ghaffar, Tahir (Journal of Postgraduate Medical Institute, 2018)
Objective: To find out the frequency of undiagnosed thyroid disorders in pa- tients with type 2 diabetes mellitus. Methodology: It was a descriptive study. One hundred and forty-two patients with age 20 years and above and of either gender who were diagnosed cases of type 2 diabetes were included in study from the outpatient department (OPD) of Hayatabad Medical Complex, Peshawar. Frequency of undiagnosed thyroid disorders was determined. Thyroid disorders were classified as clinical hyper- thyroidism, subclinical hyperthyroidism, clinical hypothyroidism and subclinical hypothyroidism. Results: Out of 142 patients, there were 78 (54.9%) females and 64 (45.1%) males. Overall undiagnosed thyroid disorders in type 2 diabetic patients were 18.3%. Subclinical hypothyroidism was 8.5%, clinical hypothyroidism was 4.9%, subclinical hyperthyroidism was 3.5% and clinical hyperthyroidism was found in 1.4% of type 2 diabetic patients. Conclusion: A high proportion of type 2 diabetic patients had undiagnosed thyroid disorders and Subclinical hypothyroidism was the most frequent thy- roid disorder.